Comparison PAPI and CAPI methods in data collection : an application of technology acceptance model (TAM) - wati, lisa (PPM Telkom University, 2023)
This research aims to comparative analysis about technology acceptance model (TAM) variables; perceived usefulness (PU), perceived ease of use (PEOU), and attitude (ATT) of interviewers in using conventional paper and pencil interview (PAPI) and computer-assisted personal interview (CAPI) as data collection methods. The data were collected from two groups of interviewer, with a total of 334 interviewers. Analyses were conducted within each group and then compared using t-test using JASP 0.17.2.1. The findings showed that the two groups of PAPI and CAPI interviewers differed in their usage of survey methods. This research will assist organizations in planning the transformation of survey methods from PAPI to CAPI. It will also contribute to the understanding of the differences in interviewers' perceptions towards these two data collection methods.